Nilai-Nilai Sosiokultural di Era Revolusi Industri 4.0 sebagai Landasan Kurikulum Pendidikan Agama Islam: Sociocultural Values in the Era of the Industrial Revolution 4.0 as the Foundation for the Islamic Religious Education Curriculum - Ismail, Irfan; Marwiji, Muh. Hasan (Perkumpulan Peneliti dan Pegiat Literasi, 2023)
This research aims to analyze Islamic education in the context of the socio-cultural challenges of the industrial revolution 4.0. This research uses a qualitative approach using a literature review, which includes legislative, historical, comparative, and conceptual aspects. The findings of this study highlight two important things, namely: First, Islamic education encourages harmony and peace by fostering tolerance. To achieve this, it requires adapting socio-cultural values, reinterpreting the Quran and Hadith, and integrating them with other approaches. This includes internalizing socio-cultural values into the learning process, which is especially important in Indonesia, a heterogeneous society with diverse ethnicities, regions and cultures. Secondly, Islamic Education recognizes the importance of social and cultural interaction in the learning process, which has a potential impact on individual development. Although it incorporates technology-based approaches and modern learning models in response to the Fourth Industrial Revolution, its primary goal remains the preservation of religious values and devotion to Allah. This research underscores the important role of Islamic Education in addressing contemporary social and technological challenges, emphasizing the integration of socio-cultural values to foster a harmonious and diverse society.